Unilateral biportal endoscopy versus microscopic decompression in the treatment of lumbar spinal stenosis: A meta-analysis. Issue 14 (7th April 2023) - Zhou, Huaqiang; Wang, Xuhua; Chen, Zhaoyuan; Liu, Wuyang; Luo, Jiaquan
Abstract : Background: The aim of this study was to evaluate whether there is a superior clinical effect of unilateral biportal endoscopy compared with microscopic decompression in the treatment of lumbar spinal stenosis. Methods: We searched CNKI, WANFANG, CQVIP, CBM, PubMed, and Web of Science up to January 2022, and selected studies that met our inclusion criteria. Results: The results of this meta-analysis indicated that unilateral biportal endoscopy was demonstrated to be more beneficial for patients compared with microscopic decompression for the following outcomes: Operation time [standardized mean difference (SMD) = −0.943, 95% confidence interval (CI) (−1.856, −0.031), P = .043], hospital stays [SMD = −2.652, 95% CI (−4.390, −0.914), P = .003], EuroQol 5-Dimension questionnaire [SMD = 0.354, 95% CI (0.070, 0.638), P = .014], back pain visual analogue score [SMD = −0.506, 95% CI (−0.861, −0.151), P = .005], leg pain visual analogue score [SMD = −0.241, 95% CI (−0.371, −.0112), P = .000], the C-reactive protein level [SMD = −1.492, 95% CI (−2.432, −0.552), P = .002]. Other outcomes demonstrated no significant differences between the 2 groups. Conclusion: For patients with lumbar spinal stenosis, unilateral biportal endoscopy was found to be more superior than microscopic decompression in terms of operation time, hospital stays, EuroQol 5-Dimension questionnaire, back visual analogue score, leg visual analogue score and the C-reactive protein level. There was no significant difference between the 2 groups in other outcome indicators.